(untitled) - Richards, Jack C (Cambridge, 1998)
New Interchange is a multi-level series for adult and young-adult learners of English from the beginning to the high-intermediate level. The Level 3 Student's Book builds on the foundations established in Level 2 for accurate and fluent communication, extending grammatical, lexical, and functional skills. Beautiful color photographs and illustrations facilitate the teaching of new vocabulary
Keywords: English language,Communication, International,Tiếng Anh,Giao tiếp, Quốc tế